New route to synthesis of unexpected 1,5-bis(1-benzofuran-2-yl)pentane-1,5-dione derivatives: Their structure determination with spectroscopic and X-ray methods - Coskun, Demet (Elsevier, 2017)
The new 1,5-bis(1-benzofuran-2-yl)-1,5-dione derivatives were obtained by the reaction of 2 -acetyl benzofuran derivatives (1a-b) and suitable aromatic aldehyde derivatives (2-pyridinecarboxaldehyde, 2-fluoro and 3-fluorobenzaldehyde) in the presence of sodium hydroxide as the base. Importantly, a new process was explored for the synthesis of new bis benzofuran dione derivatives. The structures of the compounds was identified with infrared (IR), H-1-NMR, C-13-NMR, HSQC and HMBC spectroscopic methods and elemental analysis. A representative X-ray crystallographic analysis of 3c was given, and its X-ray data were discussed in detail. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Bisbenzofurandione; Michael addition; X-ray diffraction